Qualidade de vida relacionada à saúde em pacientes acometidos por doença inflamatória intestinal tratados com terapia biológica - Silva, Isabel Cristina Lopes da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Inflammatory bowel diseases are becoming a major public health problem in Brazil and worldwide. Although their incidence is relatively low, studies show that young people of working age are affected by this disease characterized by periods of activity and remission amending of impactful quality of life. The conventional medical treatment includes the use of immunosuppressive and immunoregulatory agents.It stands out among these treatments biological therapy, represented by the class of tumor necrosis drugs (anti-TNF α). Objective: To correlate the clinical response to the quality of life of patients with inflammatory disease treated with biologic therapy. Methods: A prospective longitudinal study conducted at the Hospital of the Botucatu School of Medicine / UNESP, which evaluated 35 patients with inflammatory bowel disease using biological therapy through Inflammatory quality of life questionnaires Bowel Disease Questionnaire(IBDQ) and Crohn's disease activity index (DC), and CDAI score of Mayo for Ulcerative Colitis and Montreal Rating disease at weeks 0, 14,30,54 Results: 42,8% of the study population were female, 57,2% male, 94,3% white, 17,1% were smokers, and 77,1% were affected by Crohn's disease (CD) and 22.8% Colitis Colitis (UC). Of these patients 65, 7% made use of Infliximab and 34,3% of Adalimumab. The mean disease duration was 6,1 years (± 5,0). Clinical remission with symptom improvement and healing of the intestinal mucosa was achieved by 80% of patients. Perianal manifestations were observed in 44,4 %%, 25,7% required hospitalization, surgery 25,7%, 2,9% progressed to death. In responding patients showed a statistically significant improvement in all the applied life quality scores

As doenças inflamatórias intestinais vêm se tornando um importante problema de saúde pública no Brasil e no mundo. Embora sua incidência seja relativamente baixa, estudos mostram que pessoas jovens, em idade produtiva são acometidas por essa patologia caracterizada por períodos de atividade e remissão, que altera de forma impactante a qualidade de vida. O tratamento clínico convencional compreende o uso de agentes imunossupressores e imunorreguladores. Destaca-se dentre esses tratamentos a terapia biológica, representada pela classe de fármacos anti fator de necrose tumoral (anti- TNF α). Objetivo: Correlacionar a resposta clínica à qualidade de vida dos pacientes com doença inflamatória tratados com terapia biológica. Métodos: Estudo prospectivo longitudinal realizado no Hospital das Clínicas da Faculdade de Medicina de Botucatu/UNESP, no qual foram avaliados 35 pacientes com doença inflamatória intestinal em uso de terapia biológica, através de questionários de qualidade de vida Inflammatory Bowel Disease Questionnaire (IBDQ) e índices de atividade da Doença de Crohn (DC) CDAI e Escore de Mayo para Retocolite Ulcerativa e Classificação de Montreal doença nas semanas 0, 14,30,54. Resultados: Da população estudada 42,8% eram mulheres, 57,2% homens, 94,3% brancos, 17,1% eram tabagistas, sendo que 77,1% eram acometidos por Doença de Crohn (DC) e 22,8% Retocolite Ulcerativa (RCU). Desses pacientes 65,7% fizeram uso do Infliximabe e 34,3% do Adalimumabe. O tempo médio de doença foi de 6,1 anos (±5,0). Remissão clínica com melhora dos sintomas e cicatrização da mucosa intestinal foi alcançada por 80%dos pacientes. Manifestações perianais foram observadas em 44,4%%, necessitaram de internação 25,7%, cirurgia 25,7%, evoluiu para óbito 2,9%. Nos pacientes respondedores houve melhora estatisticamente significativa em todos os índices de qualidade de vida aplicados. Conclusão: O presente estudo apontou que a...
Keywords: Intestinos - Doenças; Doenças inflamatórias intestinais; Pacientes; Qualidade de vida; Terapia biológica; Imunoterapia; Biological Therapy; Inflammatory bowel deseases